Personal Hygiene Practices and Blood Cholinesterase Activity among Tobacco Pesticide Sprayers in Rural Indonesia - Raden Bagus Asyim; Zetiawan Trisno; Ardhanita Qalbani Putri (ANTHOR: Education and Learning Journal, 2025)
Pesticide sprayers are at high risk of occupational exposure, particularly in rural agricultural settings where preventive measures are limited. Personal hygiene practices may play a critical role in reducing internal pesticide exposure, yet biomarker-based evidence from rural Indonesia remains scarce. This study aimed to examine the association between personal hygiene practices and blood cholinesterase activity among tobacco pesticide sprayers in rural Indonesia and to describe related health complaints. A cross-sectional study was conducted among 20 tobacco pesticide sprayers in Jelbudan Village, East Java, Indonesia, using a total sampling approach. Personal hygiene practices and health complaints were assessed through structured interviews. Blood cholinesterase activity was measured using a Tintometer kit and categorized according to standard reference values. Data were analyzed descriptively and using prevalence ratios to assess associations. Inadequate personal hygiene practices were common, particularly failure to wash hands with soap after spraying (55%). Mild cholinesterase inhibition was observed in 60% of participants. Sprayers who did not wash their hands immediately after spraying had a higher prevalence of reduced cholinesterase activity (PR = 1.84) than those who washed their hands properly. Headache, dizziness, and shortness of breath were the most frequently reported health complaints, although their association with cholinesterase activity was weak. Poor personal hygiene practices are prevalent among tobacco pesticide sprayers and are associated with reduced blood cholinesterase activity. Promoting basic hygiene behaviors and routine biomonitoring may help reduce occupational pesticide exposure in rural agricultural communities.